Design and Validation of a Scale for Measuring Well-Being of Children in Lockdown (WCL) - Berasategi, Naiara; Idoiaga, Nahia; Dosil, Maria; Eiguren, Amaia (Frontiers in Psychology, 2020)
The objective of this study was to create and validate an instrument to measure the wellbeing of children in lockdown. As a response to the COVID-19 pandemic, and in the interest of maintaining social distancing, millions of people have been confined to their homes, including children, who have been withdrawn from school and barely able to leave their homes. Thus, it would be useful to evaluate, from a holistic perspective, the well-being of children under these challenging circumstances. The participants were 1046 children 48.7% of which were boys and 50.7% girls, recruited in the Basque Country (Northern Spain). The survey, entitled, 'Well-being of Children in Lockdown" (WCL) is composed of six sub-scales: Emotions, Playful and creative activities, Education, Addictions, Routine, and Physical Activity. Exploratory factor analyses indicate that all the reliability indices were acceptable. The survey demonstrated adequate reliability (alpha=.804). We were thus able to confirm the validity of this simple instrument for evaluating the well-being of children aged between 4 and 12 years in lockdown situations.2